The Insult - Thomson R. Rupert (London, Bloomsbury, 1996)
As Martin Blom walks to his car one evening, he is shot and consequently loses his sight. His surgeon tells him to expect feelings of shock, depression and self-pity. But while in the clinic gardens one evening, something miraculous happens. Rupert Thompson is the author of Air and Fire.